Pengembangan E-Commerce dengan Integrasi API Payment Gateway Midtrans - Gani Kharisma Wardana; Bayu Rahayudi; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Toko Arofah is a store in Surabaya that sells a variety of typical Arabian snacks and native Arabian herbal medicines. Currently, the sales are only carried out through the store directly and the promotion process is carried out via WhatsApp. That way is indeed less effective especially in the current pandemic season where everyone has to carry out social distancing. This has an impact on decreasing revenue at Arofah Shop and for customers also experiencing difficulties in getting herbal medicine or Arabian snacks. To facilitate this, an e-commerce website was built using the prototype method complete with features of product management, admin, and transaction management systems. In addition, integration with Midtrans, a payment gateway transaction payment service provider, is also carried out. This website is tested using black-box testing and usability testing. From the test results, it is found that the website can be easily learned and used by admins and users.